Alleviation of stale information in weak cache coherence for wireless www - Ahmad, Nazrul M.; Tan, Kim-Geok; Abdelrahman, Ali M. (Universiti Utara Malaysia, 2006)
In this paper, we identify the client polling as a cache coherence mechanism that best satisfies the requirements and improves the performance of web services over wireless networks. However, this mechanism suffers from degradation of client satisfaction by potentially sending stale information. Therefore, we propose a conceptual framework, Multilevel Pre-fetching (MLP), to alleviate the stale information forwarded by the web cache to the clients. The MLP is responsible for improving the level of freshness among the cached objects by pre-fetching the most frequently accessed objects.